Fpr2/CXCL1/2 Controls Rapid Neutrophil Infiltration to Inhibit Streptococcus agalactiae Infection - Zeyu Sun (Frontiers Media S.A., 2021)
Streptococcus agalactiae, also known as group B streptococcus (GBS), can cause pneumonia, meningitis, and bacteremia, making it a pathogen that can increase the risk of death in newborns and immunodeficient individuals. Neutrophils are the first barrier to a host’s innate immune defense against these infections. Fpr2(Formyl peptide receptor 2) is an important chemotactic receptor of neutrophils, though its activation would cause pro- and anti-inflammatory effects. In this study, we found that mice without Fpr2 receptor were highly susceptible to GBS infections. These mice demonstrated decreased chemotaxis to neutrophils, decreased bactericidal ability of neutrophils, and high mortality. RNA-seq and Luminex assay indicated that Fpr2 activates key signal molecules downstream and produces chemokines CXCL1/2 to chemotaxis neutrophils. Like Fpr2-/-, CXCL1/2 or neutrophil depletion impairs host’s ability to defend against GBS infection. Altogether, these data indicate that Fpr2 contributes to a host’s ability to control GBS infection and that a lack of Fpr2 was associated with selective impairment during the production of chemokines CXCL1 and CXCL2 as well as neutrophil recruitment. Here, We clarified that Fpr2, as a chemotactic receptor, could not only directly chemotactic neutrophils, but also regulate the production of chemokines to control infection by chemotactic neutrophils.